2020
DOI: 10.3233/jad-200098
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Demonstrate Local Mixed Inflammation and a Defined Morphological Shift in an APP/PS1 Mouse Model

Abstract: Background: Microglia are traditionally described as the immune cells of the brain and have an inflammatory role in Alzheimer’s disease (AD). Microglial morphological and phenotypic shifts in AD have not been fully characterized; however, microglia are often described as either pro- or anti-inflammatory. Objective: To determine microglial if microglial morphology and phenotype changes with disease status. Methods: This study observed morphology through Iba1 immunohistochemistry on tissue sections encompassing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Interestingly, bipolar/rod-shaped microglia in various subcortical regions of AD brains displayed high immunoreactivity against tau protein, suggesting that they might be involved in the internalization of NFTs or degenerating neurons with high loads of hyperphosphorylated tau ( Odawara et al, 1995 ). Similarly, bipolar/rod-shaped microglia were also found in aged chimpanzees with AD-like pathology ( Edler et al, 2018 ), and APP/PS-1 mouse model of AD ( Holloway et al, 2020 ). Interestingly, a recent study demonstrated that the occurrence of bipolar/rod-shaped microglia in cerebral cortex and hippocampus increased with age.…”
Section: Bipolar/rod-shaped Microglia In Alzheimer’s Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, bipolar/rod-shaped microglia in various subcortical regions of AD brains displayed high immunoreactivity against tau protein, suggesting that they might be involved in the internalization of NFTs or degenerating neurons with high loads of hyperphosphorylated tau ( Odawara et al, 1995 ). Similarly, bipolar/rod-shaped microglia were also found in aged chimpanzees with AD-like pathology ( Edler et al, 2018 ), and APP/PS-1 mouse model of AD ( Holloway et al, 2020 ). Interestingly, a recent study demonstrated that the occurrence of bipolar/rod-shaped microglia in cerebral cortex and hippocampus increased with age.…”
Section: Bipolar/rod-shaped Microglia In Alzheimer’s Diseasementioning
confidence: 92%
“…Over the past decades, much effort has been attributed to characterize ramified (resting) and amoeboid (activated) microglia in various neurological disorders that might be an oversimplification. Apart from the classical subdivision of microglia into ramified and amoeboid microglia, bipolar/rod-shaped microglia also appeared in the brains under several pathological conditions ( Ziebell et al, 2012 ; Taylor et al, 2014 ; Au and Ma, 2017 , 2022 ; Bachstetter et al, 2017 ; Edler et al, 2018 ; Holloway et al, 2020 ). In fact, bipolar/rod-shaped microglia was the first form of activated microglia characterized by Nissl in 1899 ( Nissl, 1899 ).…”
Section: Bipolar/rod-shaped Microglia In Alzheimer’s Diseasementioning
confidence: 99%